2011
DOI: 10.1111/j.1744-9987.2011.00953.x
|View full text |Cite
|
Sign up to set email alerts
|

High Cut‐Off Membrane Hemodiafiltration in Myoglobinuric Acute Renal Failure: A Case Series

Abstract: Acute renal failure is a major complication of rhabdomyolysis. New membranes for hemodialysis have been developed with a high cut-off pore size allowing efficient removal of myoglobin. We report on six patients treated by hemodiafiltration with a high cut-off membrane (HCO-HDF) for myoglobinuric acute renal failure. Rhabdomyolysis was caused by infection in two patients, by a statin in one patient and a non-traumatic crush in another, and followed cardiovascular surgery in two others. Ten HCO-HDF procedures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 21 publications
2
38
0
Order By: Relevance
“…HCO devices are CE certified and used in different clinical indications, among them elimination of cytokines in sepsis or serum free light chains in multiple myeloma. Only recently, improved myoglobin elimination has been reported for these filters in individual cases [25,26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…HCO devices are CE certified and used in different clinical indications, among them elimination of cytokines in sepsis or serum free light chains in multiple myeloma. Only recently, improved myoglobin elimination has been reported for these filters in individual cases [25,26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HCO showed an increased retention onset, defined as the mean value of the molecular weight of those molecules with an SC equal to 0.9, clinically represented by the molecular weight of the smallest molecule which is subjected to transmembrane retention. The higher retention onset allows to increase and maintain clearance of molecules with a lower molecular weight for longer periods of time, that is, myoglobin (18 kDa) [12], β2-microglobulin (12 kDa) [13], and interleukin-8 (8 kDa) [14]. The adhesion of proteins to the membrane surface commonly occurs during the treatment, and this new layer (‘protein cake') acts as a barrier that further affects the transmembrane clearance by means of pore occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies evaluating hemofiltration for myoglobin clearance have been small and contradictory [8,9,10,11,12,13,14,15,16,17,18] (table 3). Similar to ours, in these studies the sieving coefficient was greater at the beginning of the treatment and decreased over time.…”
Section: Discussionmentioning
confidence: 99%
“…It appears in the urine only when the renal threshold of 0.5-1.5 mg/dl of myoglobin is exceeded and is visible (as dark urine) when 100 mg/dl of myoglobin is reached [2]. In addition to standard medical care including aggressive volume resuscitation and urinary alkalinization, it has been suggested that elimination of myoglobin might be enhanced by a blood purification modality based on convective clearance and that its removal will decrease the risk of AKI in high-risk patients [8,9,10,11,12,13,14,15,16]. It remains controversial whether or not significant clearance can be obtained beyond that achieved through both renal and extrarenal mechanisms.…”
Section: Introductionmentioning
confidence: 99%